The Influence of Promotion Strategies through Social Media on Purchasing Decisions of Oriflame Products on Students of STIE Mikroskil Medan - M. Yamin Siregar; Weny Weny; Eko Yuliawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research aims to know the influence of promotion strategies of Facebook, YouTube, Twitter and Instagram on the decision to purchase Oriflame product on students of STIE – Mikroskil Medan. Population sampled in this research is students of STIE – Mikroskil Medan as many as 89 people with random sampling technique. Data analysis method which is used in this research is multiple linear regression analysis. The results of this study is Facebook, YouTube, and Instagram have positive and significant effect on purchasing decision Oriflame product. While the variable of Twitter does not have positive and significant effect decision on purchasing decision Oriflame product. Furthermore, simultaneous test results (F–tests) shows that the four independent variables (Facebook, YouTube, Twitter and Instagram) have a positive and significant effect on the decision of purchasing Oriflame product. Adjusted r square shows that Facebook, YouTube, Twitter and Instagram can explain variation on purchasing decision variable is 44.7% and the rest of 55.3% is explained by other variables which are not observed in this research.